Effect of pyramidal dome geometry on the acoustical characteristics in a mosque - Azma, Putra; Kassim, Dg Hafizah; Mohd Nor, Mohd Jailani; N. S. Muhammad (Universiti Malaysia Pahang, 2014)
As an important symbol in Islam, a mosque is built with architectural grandeur. Among the characteristics is its high ceiling and it is usually constructed with a typical spherical dome shape. Some mosques, however, are influenced by the local culture and the dome can be of a different shape, such as pyramidal, as found in mosques in Malacca, Malaysia. This paper presents an assessment of the internal acoustical characteristics of a mosque having a pyramidal dome. The study is conducted by means of computer simulation using CATT indoor acoustic software. Reverberation time and clarity are taken to evaluate the intelligibility of speech. The effect of the angle and height of the dome on the acoustical parameters is discussed. It is found that a pyramidal dome with a steeper angle contributes to poor acoustic clarity.